Village Head's Leadership in Strengthening Multiple Case-Based Village Libraries in Java - Rachman, Rani (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study examines the pivotal role of village heads in strengthening socially sustainable village libraries. It highlights how village heads act as facilitators of community solidarity, strategic policymakers in literacy development, infrastructure developers, and transformative leaders who actively engage younger generations. Employing a qualitative multiple-case study approach, data were collected through in-depth interviews with village heads and library managers in three village libraries across Java. A cross-case thematic analysis was conducted to identify challenges, successes, and best practices in managing village libraries within diverse social and cultural contexts. The findings reveal that village heads play a crucial role in advancing community literacy and well-being. By fostering a strong sense of togetherness, they encourage active community participation in literacy programs. Their strategic decisions further contribute to the sustainability of village libraries through financial support and literacy-oriented policies. In addition, the involvement of village heads in infrastructure development ensures that libraries function as comfortable and inclusive spaces for learning and knowledge-sharing. Equally important, their leadership in fostering youth participation strengthens libraries' role as centers of innovation and lifelong learning. While this research provides valuable insights, its scope remains limited to specific regions and does not address the long-term impacts of village head leadership on literacy development. Future studies are therefore needed to examine village libraries within broader policy frameworks and to consider longitudinal approaches for evaluating sustainability and effectiveness. The study also offers practical recommendations for village heads to optimize their support and initiatives in strengthening village libraries. Reinforced policies and greater community engagement are expected to enhance local literacy efforts and foster grassroots community empowerment.AbstrakPenelitian ini mengkaji peran penting kepala desa dalam penguatan perpustakaan desa yang berkelanjutan secara sosial. Penelitian ini menyoroti bagaimana kepala desa berperan sebagai penggerak fasilitator dalam solidaritas masyarakat, pembuat kebijakan strategis dalam pengembangan literasi, pengembang infrastruktur, serta pemimpin transformatif yang aktif melibatkan generasi muda. Dengan pendekatan studi kasus ganda dalam penelitian kualitatif, penelitian ini mengumpulkan data melalui wawancara mendalam dengan kepala desa dan pengelola perpustakaan di tiga perpustakaan desa yang berada di Jawa. Analisis tematik lintas-kasus digunakan untuk mengidentifikasi tantangan, keberhasilan, dan praktik terbaik dalam pengelolaan perpustakaan desa di berbagai konteks sosial dan budaya. Hasil penelitian menunjukkan bahwa kepala desa memiliki peran kunci dalam meningkatkan literasi dan kesejahteraan masyarakat. Dengan membangun rasa kebersamaan yang kuat, mendorong partisipasi aktif masyarakat dalam berbagai program literasi. Keputusan strategis yang diambil juga berkontribusi pada keberlanjutan perpustakaan desa melalui dukungan pendanaan dan kebijakan yang berpihak pada literasi. Selain itu, keterlibatan kepala desa dalam pengembangan infrastruktur memastikan perpustakaan menjadi ruang yang nyaman dan fungsional sebagai pusat pembelajaran dan berbagi pengetahuan. Yang tidak kalah penting, kepemimpinan kepala desa khususnya dalam merangkul generasi muda, memperkuat peran perpustakaan sebagai pusat inovasi dan pembelajaran sepanjang hayat. Penelitian ini memberikan wawasan yang cukup mendalam, namun cakupannya masih terbatas pada wilayah tertentu dan belum mengkaji dampak jangka panjang kepemimpinan kepala desa terhadap pengembangan literasi. Oleh karena itu, penelitian di masa depan perlu melihat peran perpustakaan desa dalam konteks kebijakan yang lebih luas serta mempertimbangkan studi jangka panjang untuk menilai keberlanjutan dan efektivitasnya. Temuan ini juga memberikan rekomendasi praktis bagi kepala desa agar lebih optimal dalam mendukung dan mengembangkan perpustakaan desa. Penguatan kebijakan serta peningkatan keterlibatan masyarakat diharapkan dapat semakin memperkuat upaya literasi dan pemberdayaan komunitas di tingkat lokal.